Basic research and practical applications of manganese and chromium complexes - Crewdson, Patrick (University of Ottawa (Canada), 2007)
This thesis was aimed at exploring a few selected aspects of manganese chemistry with a particular emphasis on the unconventional reactivity for this metal. Firstly, appropriate organomanganese complexes have been prepared and fully characterized. The majority of these species stemmed from our development of the effective reagent [Mn(CH2SiMe3)2(THF)] 2 which was used as starting material in ligand metathesis reactions with protic organic ligands. Two such ligands specifically designed for this purpose were the hemi-labile N-MeDipyrrole and N-MeTripyrrole ligands. These ligand systems, and various others, allowed for the synthesis of several model systems to mimic the water oxidation reaction of the OEC in Photosystem II. One such ligand (tartaric acid) formed the complex [Mn(mu3,eta 2-O2CCH(O)CH(O)CO2)(H2O)0.5]·H 2O1.5 which evolves oxygen upon addition of a strong oxidizing agent, thus indicating the oxidation of water. In another practical application for Mn(II) complexes we probed the analogy between the high spin d5 electronic configuration with the d10 electron configuration of Zn by finding for the first time Mn complexes capable of acting as catalysts in the co-polymerization of CO2 with an epoxide, producing nearly perfectly alternating polycarbonate. These findings prove that Mn is capable of catalyzing a reaction which is normally only performed by the late transition metal Zn. Similarly, we probed the behavior of Mn complexes of the bis-iminato pyridine ligand system which so effectively supports ethylene polymerization with a variety of metals. Our research into the reduction of Mn(II) complexes has led to the formation of the formally monovalent [(BisImine)MnCl(THF)] complex. At the end of the thesis we have taken advantage of the synthesis of the novel hemi-labile pyrrolide ligands for the preparation of chromium catalysts for selective ethylene trimerization reaction. The main task was to elucidate the factors which determine selectivity in the oligomerization process. At this preliminary stage we targeted the issue of metal oxidation state. It was found that both Cr(II) and Cr(III) complexes of this ligand were highly active for the production of 1-hexene, but yielded a Shultz-Flory distribution of alpha-olefins. In addition, various imine-based ligands in conjunction with Cr(II) were also found to produce statistical distributions of alpha-olefins. This work led us to revisit the selective processes published in the literature with known SNS and PNP-based compounds of both Cr(II) and Cr(III) . Overall, we were unable to unequivocally identify which oxidation state led to the selective formation of 1-hexene, our results instead indicated that selectivity might be entirely ligand-based and independent of the actual oxidation state.
Keywords: Chemistry, Inorganic.